1998
DOI: 10.1287/mksc.17.4.406
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Consumer Demand with Stock-Out Based Substitution: An Application to Vending Machine Products

Abstract: The occurrence of temporary stock-outs at retail is common in frequently purchased product categories. Available empirical evidence suggests that when faced with stock-outs, consumers are often willing to buy substitute items. An important implication of this consumer behavior is that observed sales of an item no longer provide a good measure of its core demand rate. Sales of items that stock-out are right-censored, while sales of other items are inflated because of substitutions. Knowledge of the true demand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
98
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(100 citation statements)
references
References 14 publications
0
98
0
2
Order By: Relevance
“…Lippman and McCardle (1997) study a decentralized model where the aggregate demand for all firms is a random variable and demand for each firm results from an initial allocation and very general forms of reallocation of excess demand. Anupindi et al (1998) propose a model to estimate substitution probabilities and apply it to vending machines. For a more comprehensive survey of research on demand substitution, the reader is referred to Mahajan and van Ryzin (1999).…”
Section: Introductionmentioning
confidence: 99%
“…Lippman and McCardle (1997) study a decentralized model where the aggregate demand for all firms is a random variable and demand for each firm results from an initial allocation and very general forms of reallocation of excess demand. Anupindi et al (1998) propose a model to estimate substitution probabilities and apply it to vending machines. For a more comprehensive survey of research on demand substitution, the reader is referred to Mahajan and van Ryzin (1999).…”
Section: Introductionmentioning
confidence: 99%
“…A survey report of Anupindi et al (1998) also observed the same phenomenon, in which he found that 82-88% of buyer would be willing to buy the substitute items if the desired items are out of stock. The substitutable items in which sufficient deterioration can take place during the normal storage period of the units and consequently this loss must be taken into account when analyzing the inventory system of substitutable items, i.e.…”
Section: Introductionmentioning
confidence: 68%
“…Anupindi et al (1998), Chong et al (2001) Bell et al (2005, Kök and Fisher (2007) and Vulcano et al (2009) estimate demand as part of an assortment optimization process, and are discussed below.…”
Section: Literature Reviewmentioning
confidence: 99%